Comprehensive investigation of the mechanism for Cr(VI) removal from contaminated water using coconut husk as a biosorbent. (10th September 2021) - Verma, Renuka; Maji, Pradip K.; Sarkar, Sudipta
Abstract: It is known that some organic materials show a good capacity for selective removal of Cr(VI) from contaminated water; however, the exact mechanism of such removal has yet to be investigated and established. In this study, coconut husk, a waste material with no or low cost, has been used as a representative material to investigate the exact mechanism of Cr(VI) removal by organic matter from synthetic wastewater. The investigation has been carried out in two significant stages. First, the adsorption phenomenon was studied using batch kinetic and column studies to determine the isotherms and kinetic models and effects of process parameters like solution pH and contact time. 100% Cr(VI) removal was achieved at pH 2 within 30 min at a stirring rate of 300 rpm. Although an impressive adsorption capacity of 222.22 mg/g was calculated using the Langmuir model, there was a poor fit of the observed data with the known adsorption models, leading to the inference that the mechanism of removal involved processes other than simple adsorption. The virgin and exhausted material were further characterized using field emission-scanning electron microscope (FE-SEM), thermal analysis, Attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR) and X-ray photoelectron spectroscopy (XPS). From the characterization results, it was found that Cr(VI) was first adsorbed at the functional groups followed by oxidation of major components like hemicelluloses, cellulose, and lignin, present in the adsorbent, resulting in the formation of ethers, carboxylic groups, and other carbonyl functionalities. Cr(VI) itself got reduced to Cr(III) and precipitated as Cr(OH)3 inside the pores of the adsorbent. The study conclusively established that Cr(VI) removal by organic matters such as coconut husk is essentially a sorption coupled redox process. Graphical abstract: Image 1 Highlights: Cr(VI) removal was investigated by coconut husk as a representative biosorbent. 100% Cr(VI) removal was achieved at pH 2 in batch adsorption study. Cr(VI) was reduced to Cr(III) while the components of coconut husk were oxidized. Sorption coupled with redox reaction was found responsible for Cr(VI) removal. The removal mechanism may inspire the design of high-capacity adsorbents for Cr(VI).